Systematics of Literature Reviews: Learning Model of Discovery Learning in Science Learning - Yayat Suharyat; Tomi Apra Santosa; Zulyusri Zulyusri; Suhaimi Suhaimi; Sanju Aprilisia (LITERACY : International Scientific Journals of Social, Education, Humanities, 2022)
The development of the 21st century has affected the world of education. Current education students must be led to learn more creatively and actively. This study aims Furthermore, a teacher is able to encourage learning motivation in learning science. Science learning is a compulsory subject in schools. In learning science, students must think more critically and scientifically. It aims to enable students to solve scientific problems. However, students are still less active in learning, student learning outcomes are low and student motivation in learning science is low. So, teachers are expected to be able to adopt a learning model that can make students more active and motivated in learning. The learning model of discovery learning is a learning model that supports the quality of student learning in science learning. This research is a type of systematic literature review research. The research data comes from analysis of national or international journals that have links with discovery learning models in science learning. Data collection was carried out by direct observation by observing related journals. Data search through the Google Scholar, ScienceDirect, Wiley, Eric and Springer databases. The keywords used in tracing data sources are discovery learning models, science learning and learning. The analysis technique is descriptive qualitative analysis with the PRISMA model. The results of the study concluded that the discovery learning learning model was able to improve learning outcomes and motivation in learning. Furthermore, the discovery learning learning model becomes a learning model that is able to support the quality of students in learning science. In addition, this learning model is able to make students more active in learning.